Pendampingan UMKM: Literasi dalam Pengelolaan Manajemen UMKM Kuliner di Desa Wayame: Pengabdian - Asnawi, Aisah; Melati Arifin, Hasmia; Theresia Waileruny, Hulawa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The culinary sector is one of the key sectors that significantly contributes to economic growth, particularly at the local level. However, culinary MSMEs still face various management challenges, especially in marketing, finance, and business operations. This community service activity aims to map and provide assistance to culinary MSMEs in Ambon City that have been operating for at least three years. Out of a total of 50 MSMEs mapped, five were selected as samples based on the following criteria: (1) not yet adopting digitalization in marketing, (2) not yet implementing financial recording, and (3) experiencing operational constraints. The assistance was carried out over three months using a practical management approach. The results of the program indicate an improvement in the understanding and skills of MSME owners in managing their businesses more systematically, particularly in the use of digital media, financial recording, and operational flow improvement. It is expected that this program will enhance the income and competitiveness of culinary MSMEs amid intense business competition.